Skeletal muscle regeneration in DNM2-related centronuclear myopathy - Almeida, Camila de Freitas (2019)
The skeletal muscle has a remarkable regenerative capacity upon injury, due to the presence of the satellite cells, which remain quiescent in the tissue, but, when required, they are able to proliferate and form and/or repair myofibers. Moreover, satellite cells are important to muscle growth and maintenance. However, in many neuromuscular disorders, the amount, function, and proliferative capacity of these cells are impaired. Centronuclear myopathies (CNM) are a group of muscle diseases characterized by generalized muscle weakness and myofibers with central nuclei. The autosomal dominant form (AD-CNM) is caused by mutations in the DNM2 gene. Dynamin 2 protein is ubiquitously expressed and is involved in membrane remodeling, intracellular trafficking, and cytoskeleton dynamics. Therefore, the pathophysiological mechanisms are equally diverse e not completely understood, mainly the fact to be a muscle-specific disease. In the present Ph.D. thesis, we sought to investigate the satellite cells in the context of centronuclear myopathy. For this, we used the mouse model KI-Dnm2R465W, bearing the most frequent mutation found in human patients. Since in centronuclear myopathy there is no evident degenerative process ongoing, we induced muscle lesion by electrical shock, a protocol developed for this thesis, comparatively to cardiotoxin injection. We verified that the number of satellite cells in gastrocnemius muscle is reduced in the KI-Dnm2R465W mouse in relation to wild-type animals. As a result, the regenerative potential of the mutant mouse is decreased and the muscle is not able to fully recover. In addition, we investigated the functional consequences of two mutations, p.R465W and p.E650K, in immortalized myoblasts. We examined the myogenic potential in vitro, the migratory property, and the endocytosis capacity. We found that both mutations impact on the myogenic potential, but in different ways. We also show that both mutations impair the migratory capacity of myoblasts that justify, in parts, the alterations in their myogenic potential. Finally, we verified that the endocytosis capacity is affected in a mutation-dependent manner, which may also indirectly disturb the myogenic differentiation efficiency